The cultural sustainability in English as foreign language textbooks: Investigating the cultural representations in English language textbooks in China for senior middle school students - Lu, Jun; Liu, Yanhong; An, Lin; Zhang, Ying (Frontiers in Psychology, 2022)
In the age of globalization, studies of cultural representations in foreign language textbooks take account of cultural sustainability. This paper reports on a case study of cultural representation in two English language textbook series that are widely used in senior high schools in China. The study investigated whether the cultural representations in these textbooks contribute to the development of local cultural sustainability. Content analysis was employed to examine the texts used in these textbooks, with references to the synergy of the theoretical frameworks of Laine’s (2016) cultural sustainability and Kachru’s (1992) world Englishes. The study results indicate that there is an imbalanced cultural representation with respect to the categories of International Cultures and National Culture in these textbooks. The results point to the cultures of the Inner-circle countries (BANA: Britain, Australasia, North America) being predominant, while the representation of Chinese culture has a low profile. As these textbooks are an important learning and teaching resource in China, they have the potential to play a significant role in influencing learners’ worldviews as they develop their understanding of different cultures. The imbalanced presentation of culture may in turn lead to a biased worldview where learners, rather appreciating cultural diversity, may instead discriminate against certain cultures (Song, 2013).The implications for redressing the imbalance in cultural representation and cultural sustainability are discussed.